Estudo comparativo de topologias de inversores para a conexão de painéis fotovoltaicos com a rede elétrica sem o uso de transformador - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This course conclusion work presents a study and a comparative analysis between different topologies of single-phase inverters for connecting solar panels to the grid without transformer use. Analyzes were conducted on the size of the inductive output filter, the losses in the semiconductor devices, the efficiency and the leakage current. These analyzes will be carried out with input parameters of the inverters for different solar radiations. Data analysis has the ultimate objective assessment of which of the studied topologies is more recommended the use of solar photovoltaic power generation with interconnection to the grid systems. They are taken into account the advantages and disadvantages of each topology for each of the variables evaluated.
Keywords: Electrical engineering; Electric motors; Photovoltaic systems; Electrical networks; Engenharia elétrica; Redes elétricas; CNPQ::ENGENHARIAS; Inversores elétricos; Sistemas fotovoltaicos